Seasonal Changes and Spatial Variation in Water Quality of a Large Young Tropical Reservoir and Its Downstream River - Ling, Teck Yee; Norliza, Gerunsin; Soo, Chen Lin; Lee, Nyanti; Sim, Siong Fong; Jongkar, Grinang (Hindawi Publishing Corporation, 2017)
This study examined the water quality of the large young tropical Bakun hydroelectric reservoir in Sarawak, Malaysia, and the influence of the outflow on the downstream river during wet and dry seasons.Water quality was determined at five stations in the reservoir at three different depths and one downstream station. The results show that seasons impacted the water quality of the Bakun Reservoir, particularly in the deeper water column. Significantly lower turbidity, SRP, and TP were found during the wet season. At 3–6m, the oxygen content fell below 5 mg/L and hypoxia was also recorded. Low NO2 −-N, NO3−-N, and SRP and high BOD5,OKN, and TPwere observed in the reservoir indicating organic pollution.Active logging activities and the damconstruction upstream resulted in water quality deterioration. The outflow decreased the temperature, DO, and pH and increased the turbidity and TSS downstream. Elevated organicmatter and nutrients downstream are attributable to domestic discharge along the river.This study shows that the downstream river was affected by the discharge through the turbines, the spillway operations, and domestic waste. Therefore, all these factors should be taken into consideration in the downstream river management for the health of the aquatic organisms.